Identificação das unidades de paisagem do município de Caçapava do Sul – RS: subsídios à interpretação geopatrimonial em roteiros geoturísticos - Madeira, Márlon Roxo (2022)
The landscapes represent the materialization resulting from the relationship between society and nature, allowing the incorporation of a holistic, dialectical and systemic vision in its study, essential as an instrument for environmental planning and territorial management. Using the geoecological approach to the landscape, landscape analysis is a territorial analysis tool that helps in initiatives for the balanced occupation of space, between anthropic appropriation and the conservation of natural structures and functionalities. According to Mateo Rodriguez; Silva (2018) landscape geoecology involves the set of natural landscapes, in their different dimensions, as its object of study. The difficult relationship between the conservation of the landscape heritage and the economic use has sparked different debates around proposals that integrate the natural heritage and the territorial development policies based on tourism. The landscape, expressing the relationship between society and nature, can and should act as a catalyst for the preservation of geodiversity, given its symbolic value and its ability to enhance awareness of different types of heritage elements that society is less sensitive to. Geotourism, as a modality of ecotourism focused on geopatrimonial interpretation, is part of the new concepts in geosciences, associated with the valorization of local communities and the endogenous economic development of the territory. In this sense, the elaboration of geotouristic routes becomes, according to Jorge (2017), an important tool in the patrimonial disclosure of a certain area, as it favors new possibilities for local development, supplying a new tourist demand. In view of the above, the objective of this research is to identify landscape variations and their respective natural attractions in the municipality of Caçapava do Sul - RS, focusing on the heritage value on the landscape scale within the study area, in order to subsidize the geotouristic practices. The methodological proposal used to achieve the general objective was based on the systemic approach to landscape, developed by Bertrand (1972) and adapted by Degrandi (2011). The methodological procedure used makes it possible to delimit homogeneous and hierarchical units of the landscape, first from their structural variations and, second, from the patterns generated by the interaction between society and nature. After defining the landscape units, the information presented by Borba et al., (2013) on the inventory and quantitative assessment the 46 geosites associated with the municipality's geological heritage will be considered, with the purpose of evaluating the geosites with high heritage values on the scale of landscape, based on the methodology proposed by Sell (2017). Thus, the main places of scenic interest and their potential for the production of future geotouristic materials were identified. In the end, it can be concluded that among the landscape units defined during the research, there is a great diversity of rock outcrops, found mainly in the residual plateaus unit with seasonal forest, which need to be protected, such as the Guaritas do Camaquã, the rocky outcrops of Serra do Segredo, among other places of scenic interest. The Caçapavano territory has environmental, historical and cultural particularities that can serve as important elements for local development, through activities associated with geotourism.